Influence of Investment Decisions, Corporate Social Responsibility and Company Growth in Companies Manufacturing of the Sub-Sector of Consumption Goods Registered in Indonesia Stock Exchange Year 2017-2019 - Sinurat, Anggiat; Damanik, Elfina Okto Posmaida; Munthe, Risma; Sriwiyanti, Eva; Martina, Sri (Budapest International Research and Critics University, 2020)
This study aims to determine the effect of investment decisions, corporate social responsibility and company growth in consumer goods manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. Several previous studies on different firm values. Therefore, other research needs to be done to retest the theory of value. The research data is obtained from sample companies which can be downloaded from the Indonesia Stock Exchange website. The data analysis technique used is multiple regression analysis. The data analysis process that is done first is the classical assumption test, multiple regression analysis and then testing the hypothesis. The results of the study partially show that only investment decisions have a positive and significant effect on firm value. Meanwhile, the growth of companies and corporate social responsibility has no effect on firm value. The results of the research simultaneously show that corporate social responsibility and company growth have a significant effect on firm value.